Faktor-Faktor Yang Menentukan Minat Mahasiswa di Kota Bandung terhadap Penggunaan Kartu Tanda Mahasiswa Terintegrasi E-Money - Alliya Az-Zahra Lukman; Ima Amaliah (Bandung Conference Series: Economics Studies)
Abstract. The digitalization of the financial sector has driven a shift in transactions from cash toward electronic money (e-money) as a non-cash payment instrument, which has now begun to be applied to Student ID Cards (KTM) at a number of universities. This study aims to identify the factors that determine student interest in Bandung City toward the use of a KTM integrated with e-money, to determine the most dominant factor, and to examine the role of respondent characteristics. This study uses a quantitative descriptive method, with primary data collected through an online Likert-scale questionnaire distributed to 100 active students from 10 universities in Bandung City, determined using the Slovin formula with a purposive sampling technique. All 22 instrument items were declared valid, with a Cronbach's Alpha value > 0.70. The descriptive analysis results show that all research variables fall into the "Very Good" category, with perceived usefulness obtaining the highest score (361), followed by perceived ease of use (351.8) and trust (335.6), making perceived usefulness the most dominant factor. Interest in using the e-money-integrated KTM is also classified as high, with a score of 357. Based on respondent characteristics, response patterns vary by gender, age, duration of use, and frequency of use, although overall all groups show a positive tendency toward interest in the e-money-integrated KTM. Abstrak. Digitalisasi sektor keuangan mendorong pergeseran transaksi dari uang tunai menuju uang elektronik (e-money) sebagai instrumen pembayaran non-tunai, yang kini mulai diterapkan pula pada Kartu Tanda Mahasiswa (KTM) di sejumlah perguruan tinggi. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang menentukan minat mahasiswa di Kota Bandung terhadap penggunaan KTM terintegrasi e-money, mengetahui faktor yang paling dominan, serta menganalisis peran karakteristik responden. Penelitian menggunakan metode kuantitatif deskriptif, dengan data primer dikumpulkan melalui kuesioner daring berskala Likert kepada 100 mahasiswa aktif dari 10 perguruan tinggi di Kota Bandung, yang ditentukan menggunakan rumus Slovin dengan teknik purposive sampling. Seluruh 22 item instrumen dinyatakan valid, dengan cronbach alpha > 0,70. Hasil analisis deskriptif menunjukkan bahwa seluruh variabel penelitian berada pada kategori “Sangat Baik”, dengan persepsi manfaat memperoleh skor tertinggi (361), diikuti persepsi kemudahan (351,8) dan kepercayaan (335,6), sehingga persepsi manfaat merupakan faktor paling dominan. Minat menggunakan KTM e-money juga tergolong tinggi dengan skor 357. Berdasarkan karakteristik responden, pola penilaian bervariasi menurut jenis kelamin, usia, lama penggunaan, dan frekuensi penggunaan, namun secara umum seluruh kelompok menunjukkan kecenderungan minat yang positif terhadap KTM terintegrasi e-money.